Petroleum refinery process modeling : integrated optimization tools and applications - Liu, Y. A.; Chang, Ai-Fu; Pashikanti, Kiran (Wiley-VCH, 2018)
The book supports operators and engineers of any experience level in how to quantitatively model key refinery reaction and fractionation processes. Chapter 1 introduces the reader to the basics of dealing with the thermodynamics and physical property predictions of hydrocarbon components in the context of process modeling. Chapters 2 and 3 use the key concepts of fractionation lumps and physical properties to develop detailed models and workflows for atmospheric (CDU) and vacuum (VDU) distillation units. Chapters 4, 5 and 6 are largely self-contained that discuss modeling FCC, catalytic reforming and hydroprocessing units.